2007
DOI: 10.1038/modpathol.3800952
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal and methylation alterations in sporadic and familial adenomatous polyposis-related duodenal carcinomas

Abstract: Primary carcinomas of the small intestine are rare and the mechanism of their pathogenesis is poorly understood. Patients with familial adenomatous polyposis (FAP) have a high risk of developing duodenal carcinomas. The aim of this study is to gain more insight into the development of duodenal carcinomas. Therefore, five FAP-related duodenal carcinomas were characterized for chromosomal and methylation alterations, which were compared to those observed in sporadic duodenal carcinomas. Comparative genomic hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 61 publications
(79 reference statements)
1
16
1
Order By: Relevance
“…The definition of clinically meaningful cutoff values is crucial. The arbitrary 20% cutoff value 33,34 has been validated in our series, whereas the 15% threshold 21 would have resulted in an increase of false-negative results. Also, we have confirmed that considering only C-and D-regions of MLH1 promoter, 36,40 yields the best performance in the diagnostic setting.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The definition of clinically meaningful cutoff values is crucial. The arbitrary 20% cutoff value 33,34 has been validated in our series, whereas the 15% threshold 21 would have resulted in an increase of false-negative results. Also, we have confirmed that considering only C-and D-regions of MLH1 promoter, 36,40 yields the best performance in the diagnostic setting.…”
Section: Discussionmentioning
confidence: 79%
“…A similar value has been proposed as a meaningful cutoff value in previous studies. 33,34 Ten replicates in two independent experiments were analyzed.…”
Section: Detection Of Somatic Alterationsmentioning
confidence: 99%
“…All three enzymes, DNMT1, DNMT3a, and DMNT3b, have been shown to be overexpressed in several tumor types, including colorectal cancer (14,19). Interestingly, both sporadic and FAP-related colon adenocarcinomas have common, for example, p16 and MGMT, as well as different, for example, PAX3, tumor-suppressor genes that are methylated, and hypermethylation seems to be a general feature of both sporadic and FAP-related carcinomas (20,21). In this study, we determined whether BRBs administered in the form of a rectal suppository and/or in combination with oral administration cause suppression of polyp development in subjects with FAP, and whether BRBs affect DNA methylation in tissues collected from these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also documented mutations of SMAD4, APC, KRAS, and β-catenin (13,(16)(17)(18), as well as epigenetic silencing of APC and gains on chromosomes 7, 8, 12, 13q, and 20q, and losses on chromosomes 2, 4, 5q, 6q, 8, 9, 15q, 17p, 18, and 21 (19,20). Studies evaluating the chromosomal aberrations in patients with concomitant small bowel adenocarcinoma and Crohn's disease or familial adenomatous polyposis have shown that the chromosomal aberrations of sporadic small bowel adenocarcinoma do not differ from patients with these predisposing conditions (19,20).…”
mentioning
confidence: 99%